Building a brain under nutritional restriction: insights on sparing and plasticity from Drosophila studies - Maurange, Cédric; Lanet, Elodie (Frontiers in Physiology, 2014)
While the growth of the developing brain is known to be well protected compared to other organs in the face of nutrient restriction, careful analysis has revealed a range of structural alterations and long-term neurological defects. Yet, despite intensive studies, little is known about the basic principles that govern brain development under nutrient deprivation. For over twenty years, Drosophila has proved to be a useful model for investigating how a functional nervous system develops from a restricted number of neural stem cells. Recently, a few studies have started to uncover molecular mechanisms as well as region-specific adaptive strategies that preserve brain functionality and neuronal repertoire under nutrient restriction, while modulating neuron numbers. Here, we review the developmental constraints that condition the response of the developing brain to nutrient restriction. We then analyze the recent Drosophila work to highlight key principles that drive sparing and plasticity in different regions of the central nervous system. As simple animal models start to build a more integrated picture, understanding how the developing brain copes with nutrient restriction could help in defining strategies to limit damage and improve brain recovery after birth.